2016
DOI: 10.1097/phm.0000000000000345
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Transcutaneous vs. End-Tidal CO2 Monitoring for Patients with Neuromuscular Disease

Abstract: Maximum PtcCO2 was significantly greater than maximum PetCO2 for both groups and, therefore, tends to be higher than PetCO2 in this population. This should be taken into consideration when assessing patients for sleep hypoventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
3
8
0
1
Order By: Relevance
“…With the availability of oximetry, and capnography to measure end-tidal CO 2 , arterial blood gas sampling is rarely if ever needed for people with NMD [ 20 ]. In addition to the discomfort, 25% of patients hyperventilate as a result of the anxiety and pain caused by the arterial puncture [ 21 ].…”
Section: Patient Evaluation Specific For Ventilatory Pump Failurementioning
confidence: 99%
“…With the availability of oximetry, and capnography to measure end-tidal CO 2 , arterial blood gas sampling is rarely if ever needed for people with NMD [ 20 ]. In addition to the discomfort, 25% of patients hyperventilate as a result of the anxiety and pain caused by the arterial puncture [ 21 ].…”
Section: Patient Evaluation Specific For Ventilatory Pump Failurementioning
confidence: 99%
“…Arterial blood gas analysis is the gold standard test for assessing PaCO 2 levels. However, it is not regarded as an appropriate screening test considering its painful and invasive nature, as well as the need for continuous catheterization 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Arterial blood gas analysis is the gold standard test for assessing PaCO 2 levels. However, it is not regarded as an appropriate screening test considering its painful and invasive nature, as well as the need for continuous catheterization 17 . Various techniques for noninvasive CO 2 level monitoring have been tested in different patient populations for diagnostic efficacy since their introduction into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…PetCO2 is also less accurate in the presence of high PaCO2 levels [20]. On the other hand, many studies have reported PetCO2 to be accurate for conditions in which the exhaled gas can be sampled within or close to the airways such as for patients whose alveolar dead space is not very large and, if using NIV/NVS, for those whose sampling is at the prongs, as in these cases, rather than via larger interfaces that dilute the sample [21]. In a study of 39 subjects with NMD, while maximum transcutaneous (Ptc) CO2 was 4 to 16 mmHg higher than EtCO2s, mean PtcCO2s was less than 1 mmHg to 7 mmHg greater [22].…”
Section: Discussionmentioning
confidence: 99%